Soviet historical genre: a bridge between past and present (Journal of history-rus, 2022)
A focus of the present paper is a comparison of the nation-state building processes in modern Russia and Kazakhstan where we are using such tool as historical genre in literature. The paradox of the modern nation-state construction is usage of the approaches that were created in 1960-70s. Here we can highlight the most intriguing puzzle of the moves in western social sciences and Soviet historical genre as fiction. Same years 1960-70s had witnessed the emergence of western post-modernist history with its abnegation of previous history written by academics. In broad context we can say that new Soviet historical genre was similar abnegation of previous Stalin’s period official history with its exaggerated role of the personality in history (inspired by Joseph Stalin), colonialism problems and anti-colonial struggle along with fabulous research done over state history in former Russian empire and Soviet Union. Thus, the focus of the history had shifted from the previous acute problems to such questions as models of transformation from “imperial” to nation-state (Kappeler 2001), constructions that were used as “mobilizing instruments” (Suny 2001) and periods of Soviet history which we can underline to differentiate culture of center and periphery elite in context of their reflections on nature of nation and state (Motyl 1997).